1988
DOI: 10.1111/j.1559-1816.1988.tb00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat and Violence: New Findings from Dallas Field Data, 1980–19811

Abstract: Research in both laboratory and field settings has suggested a link between thermal stress and violent behavior, and both linear and curvilinear models have been investigated. A dearth of field studies prompted the analysis reported here, which is based on data for some 10,000 aggravated assaults occurring the City of Dallas in 1980 (a summer of severe heat stress) and 1981. This analysis replicates and extends certain aspects of recent work by Anderson and Anderson (1984) relating to the so‐called linear and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
1
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 10 publications
4
40
1
1
Order By: Relevance
“…Finally, some implications of the results are discussed. The temperature-aggression relationship has been examined both in field studies and laboratory studies (Baron, 1972(Baron, , 1976Baron and Bell, 1975, 1976;Bell and Baron, 1976;Baron and Ransberger, 1978;Anderson and Anderson, 1984;Cotton, 1986;Kenrick and MacFarlane, 1986;Anderson, 1987;Rule, Taylor, and Dobbs, 1987;Harries and Stadler, 1988;Bell and Fusco, 1989). In particular, the field studies show a consistent pattern: uncomfortable heat (25 degrees to 30 degrees Celsius) increases aggression (see Anderson (1989) for a review of this literature).'…”
mentioning
confidence: 91%
“…Finally, some implications of the results are discussed. The temperature-aggression relationship has been examined both in field studies and laboratory studies (Baron, 1972(Baron, , 1976Baron and Bell, 1975, 1976;Bell and Baron, 1976;Baron and Ransberger, 1978;Anderson and Anderson, 1984;Cotton, 1986;Kenrick and MacFarlane, 1986;Anderson, 1987;Rule, Taylor, and Dobbs, 1987;Harries and Stadler, 1988;Bell and Fusco, 1989). In particular, the field studies show a consistent pattern: uncomfortable heat (25 degrees to 30 degrees Celsius) increases aggression (see Anderson (1989) for a review of this literature).'…”
mentioning
confidence: 91%
“…Extreme heat is just one of the facets of weather that can impact humans: 739 deaths were attributed to the 1995 Chicago, Illinois, heat wave (Klinenberg 2002); tens of thousands of deaths occurred in the 2003 heat wave across Europe (e.g., Pirard et al 2005). Oppressive heat not only impacts human health; research has also shown that it is related to aggressive behavior both in laboratory and field settings (e.g., Baron and Bell 1976;Anderson and Anderson 1984;DeFronzo 1984;Harries et al 1984;Harries and Stadler 1988;Rotton andCohn 2000a,b, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…However, although one can evaluate the relationship between weather and crime via numerous variables, DeFronzo (1984) suggested that ''inhabitants of an SMSA 'adapt' to their city's particular climatic milieu such that their annual level of criminal behavior is relatively unaffected by the fact that their SMSA is subject to more or less cold or hot weather or days of precipitation than other American cities.'' On the smaller scale, the relationship between assaults and temperature across a particular city has been studied by many researchers (e.g., Anderson and Anderson 1984;Harries et al 1984;Harries and Stadler 1988;Perry and Simpson 1987;Anderson et al 1997;Cohn and Rotton 1997;Rotton andCohn 2000a,b, 2003). Analyses have been performed using a variety of temporal and spatial characteristics that led to differing conclusions, although nearly all research has shown that as temperature increases, the number of assaults generally increase as well.…”
Section: Introductionmentioning
confidence: 98%
“…Finally, it is possible that warmer temperatures provoke violence by eliciting greater alcohol consumption (Harries and Stadler 1988). Indeed, alcohol sales tend to be highest in summer (Uitenbroek 1996), and there is strong evidence that alcohol consumption increases the risk of aggressive and violent behaviour (Bennetts and Seabrook 2008;Bushman and Cooper 1990;Ray et al 2008).…”
Section: The Mechanism Of the Temperature-violence Relationshipmentioning
confidence: 97%